ESG report and its role in the Development of Corporations - Jasurbek Gulboy oʻgʻli Abdishukurov (Science and Education, 2025)
This thesis examines importance of ESG in current global environment and projects that is being performed by big csorporations, such as Micorsoft. Microsoft’s environmental sustainability initiatives are detailed in its 2024 Environmental Sustainability Report. It assesses the company’s progress towards its 2030 commitments: becoming carbon negative, water positive, achieving zero waste, and protecting more land than it uses. The analysis highlights significant advancements in renewable energy procurement, waste reduction, and land conservation. However, it also identifies challenges, particularly in reducing Scope 3 emissions and water consumption associated with data center operations. The study underscores the importance of technological innovation, strategic partnerships, and policy advocacy in overcoming these challenges and achieving Microsoft’s sustainability goals.